Kritik Sosial Terhadap Kapitalisme: Analisis Puisi di Negeri Amplop Karya Mustofa Bisri dalam Teori Karl Marx - Nabila Aswari Lubis; Retno Anggelica Aini; Ruth Sofia Rolenza Lumban Raja (Universitas Serambi Mekkah, 2025)
This study discusses social criticism of the capitalist system in the poem Di Negeri Amplop by Mustofa Bisri. This study uses Karl Marx’s perspective on capitalism, which emphasizes the inequality of social classes and the role of bourgeois ideology in maintaining dominance through economic control. The approach used in this research is a qualitative method with a literature study, which includes analysis of the poem’s text and relevant theories. The results reveal that the poem depicts capitalism as a system that not only causes economic injustice, but also forms a social consciousness that is obedient to the power of money, where the values of justice and morality are controlled by economic mechanisms.